Pengaruh Komunikasi Vertikal dan Lingkungan Kerja Terhadap Kepuasan Kerja Guru - Rada Sari; Dessi Susanti (Jurnal Ecogen, 2020)
This assessment intends to see the influence of vertical communication and work environment on teacher job satisfaction at SMK Negeri 3 Padang. The study used three variables, namely vertical communication, work environment and job satisfaction. This assessment is a descriptive quantitative research. There is a population of 79 teachers in this study, with sampling using a total sampling technique. Then obtained a sample of 79 teachers. The data collection technique used a research questionnaire. The collected data were analyzed using multiple regression analysis, to see which component had the most dominant influence on teacher job satisfaction at SMK Negeri 3 Padang. which component had the most dominant influence on teacher job satisfaction at SMK Negeri 3 Padang. The acquisition of this study obtained: 1) vertical communication has a positive and significant impact on teacher job satisfaction at SMK Negeri 3 Padang seen from the sig value. 0.000 <0.05. 2) the work environment has a positive and significant impact on teacher job satisfaction at SMK Negeri 3 Padang as seen from the sig value. 0.000 <0.05. 3) vertical communication and work environment together have  a positive and significant influence on teacher job satisfaction at SMK Negeri 3 Padang seen from the sig value . 0.000 <0.05.Keywords : komunikasi vertikal, lingkungan kerja, kepuasan kerja